Evolution of magnetism by rolling up hexagonal boron nitride nanosheets tailored with superparamagnetic nanoparticles. Issue 5 (23rd January 2017) - Hwang, Da Young; Choi, Kyoung Hwan; Park, Jeong Eon; Suh, Dong Hack
Abstract : The rolled-up boron nitride sheets (called nanoscrolls) demonstrated enhanced magnetization under a positive direction magnetic field in the case of magnetic susceptibility. The ZFC curve for the h-BN–Fe3 O4 NP scrolls exhibited an apparent rounded maximum blocking temperature at 192 K. Abstract : Controlling tunable properties by rolling up two dimensional nanomaterials is an exciting avenue for tailoring the electronic and magnetic properties of materials at the nanoscale. We demonstrate the tailoring of a magnetic nanocomposite through hybridization with magnetic nanomaterials using hexagonal boron nitride (h-BN) templates as an effective way to evolve magnetism for the first time. Boron nitride nanosheets exhibited their typical diamagnetism, but rolled-up boron nitride sheets (called nanoscrolls) clearly have para-magnetism in the case of magnetic susceptibility. Additionally, the Fe3 O4 NP sample shows a maximum ZFC curve at about 103 K, which indicates well dispersed superparamagnetic nanoparticles. The ZFC curve for the h-BN–Fe3 O4 NP scrolls exhibited an apparent rounded maximum blocking temperature at 192 K compared to the Fe3 O4 NPs, leading to a dramatic increase in T B . These magnetic nanoscroll derivatives are remarkable materials and should be suitable for high-performance composites and nano-, medical- and electromechanical-devices.